Gemcitabine sensitizes lung cancer cells to Fas/FasL system‐mediated killing. Issue 2 (February 2014) - Siena, Liboria; Pace, Elisabetta; Ferraro, Maria; Di Sano, Caterina; Melis, Mario; Profita, Mirella; Spatafora, Mario; Gjomarkaj, Mark
Summary Gemcitabine is a chemotherapy agent commonly used in the treatment of non‐small cell lung cancer (NSCLC) that has been demonstrated to induce apoptosis in NSCLC cells by increasing functionally active Fas expression. The aim of this study was to evaluate the Fas/Fas ligand (FasL) system involvement in gemcitabine‐induced lung cancer cell killing. NSCLC H292 cells were cultured in the presence or absence of gemcitabine. FasL mRNA and protein were evaluated by real‐time PCR, and by Western blot and flow cytometry, respectively. Apoptosis of FasL‐expressing cells was evaluated by flow cytometry, and caspase‐8 and caspase‐3 activation by Western blot and a colorimetric assay. Cytotoxicity of lymphokine‐activated killer (LAK) cells and malignant pleural fluid lymphocytes against H292 cells was analysed in the presence or absence of the neutralizing anti‐Fas ZB4 antibody, by flow cytometry. Gemcitabine increased FasL mRNA and total protein expression, the percentage of H292 cells bearing membrane‐bound FasL (mFasL) and of mFasL‐positive apoptotic H292 cells, as well as caspase‐8 and caspase‐3 cleavage. Moreover, gemcitabine increased CH11‐induced caspase‐8 and caspase‐3 cleavage and proteolytic activity. Cytotoxicity of LAK cells and pleural fluid lymphocytes was increased against gemcitabine‐treated H292 cells and was partially inhibited by ZB4 antibody. These results demonstrate that gemcitabine: (i) induces up‐regulation of FasL in lung cancer cells triggering cell apoptosis via an autocrine/paracrine loop; (ii) induces a Fas‐dependent apoptosis mediated by caspase‐8 and caspase‐3 activation; (iii) enhances the sensitivity of lung cancer cells to cytotoxic activity of LAK cells and malignant pleural fluid lymphocytes, partially via Fas/FasL pathway. Our data strongly suggest an active involvement of the Fas/FasL system in gemcitabine‐induced lung cancer cell killing.